Stress Management Training (SMT) Improves Coping of Tremor-Boosting Psychosocial Stressors and Depression in Patients with Parkinson’s Disease: A Controlled Prospective Study - C. Buhmann; D. Jungnickel; E. Lehmann (Parkinson's Disease)
Background. Stress reduction and relaxation exercises are therapeutically suggested to patients with Parkinson’s disease (PD) and tremor, but data regarding efficacy or preferential methods are missing. Objective. To investigate the effect of a standardized stress management training (SMT) according to Kaluza on coping with tremor-boosting psychosocial stress factors. Methods. 8-week SMT was applied to 82 PD patients with tremor and 30 controls. Changes in stress-associated factors were measured applying four scales: Kaluza’s “warning signs for stress” and “stress-amplifying thoughts” and Beck Depression Inventory (BDI) and quality of life (PDQ-8). Short-term outcome (8 weeks) was evaluated in both groups, and long-term outcome (3–6 months) was evaluated only in PD patients. Results. At baseline, PDQ-8 was worse in PD patients compared to controls. PD patients improved significantly regarding short- and long-term outcome scores of “warning signs for stress,” “stress-amplifying thoughts,” and BDI scores, independently of disease severity or duration. Younger and male PD patients showed the best benefit. Controls improved comparably to PD patients but significantly only with respect to “stress-amplifying thoughts.” Retrospectively, 88% (29/33) of PD patients were rated SMT as helpful 12–18 months later. Self-practicing SMT exercises correlated significantly with subjectively better coping with tremor-related daily impairment and subjective short-term and long-term tremor reduction. Conclusion. SMT should be a part of therapy of PD patients with tremor.